Pengaruh Pemberian Afirmasi Positif Melalui Media Audiovisual Terhadap Tingkat Kecemasan Ibu Bersalin Kala I - Shinta Fina Setiyani; Titi Maharrani; K. Kasiati; Triana Septianti Purwanto (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
Maternity anxiety results in decreased blood flow to the uterus resulting in prolonged labor. Indonesian data shows that 107,000,000 mothers feel anxious before giving birth or 28.7%. Positive sentences spoken repeatedly are positive affirmations used to reduce anxiety. The research aims to determine the effect of giving positive affirmations through audiovisual media on the anxiety level of mothers in the first stage of labor. This type ofresearch is Quasi-Experimental pretest posttest control group. Sample of 32 mothers giving birth. The independent variable is giving positive affirmations through audiovisual media, the dependent variable is the anxiety level of mothers in the first stage of labor. The measurement of anxiety levels uses the Zung Self-Rating Anxiety Scale questionnaire. Wilcoxon Signed Ranked Test and Mann Whitney U Test for data analysis. The result of the p-value is 0.001, there is an effect of giving positive affirmations through audiovisual media on the anxiety level of mothers in the first stage of labor. Giving positive affirmations is given when the mother is not having contractions so that it is effective. Future researchers are expected to evaluate the research methodology by providing different treatment to the control group.